Differential Promoter Methylation of Macrophage Genes Is Associated With Impaired Vascular Growth in Ischemic Muscles of Hyperlipidemic and Type 2 Diabetic Mice. Issue 3 (17th July 2015) - Babu, Mohan; Durga Devi, Thota; Mäkinen, Petri; Kaikkonen, Minna; Lesch, Hanna P.; Junttila, Sini; Laiho, Asta; Ghimire, Bishwa; Gyenesei, Attila; Ylä-Herttuala, Seppo
<x xml:space="preserve">Abstract</x> Rationale: Hyperlipidemia and type 2 diabetes mellitus (T2DM) severely impair adaptive vascular growth responses in ischemic muscles. This is largely attributed to dysregulated gene expression, although details of the changes are unknown. Objective: To define the role of promoter methylation in adaptive vascular growth in hyperlipidemia (LDLR–/–ApoB100/100) and T2DM (IGF-II/LDLR–/–ApoB100/100) mouse models of hindlimb ischemia. Methods and Results: Unilateral hindlimb ischemia was induced by ligating femoral artery. Perfusion was assessed using ultrasound, and capillary and arteriole parameters were assessed using immunohistochemistry. Genome-wide methylated DNA sequencing was performed with DNA isolated from ischemic muscle, tissue macrophages (Mφs), and endothelial cells. Compared with the controls, hyperlipidemia and T2DM mice showed impaired perfusion recovery, which was associated with impaired angiogenesis and arteriogenesis. Genome-wide proximal promoter DNA methylation analysis suggested differential patterns of methylation in Mφ genes in ischemic muscles. Classically activated M1-Mφ gene promoters, including Cfb, Serping1, and Tnfsf15, were significantly hypomethylated, whereas alternatively activated M2-Mφ gene promoters, including Nrp1, Cxcr4, Plxnd1, Arg1, Cdk18, and Fes, were significantly hypermethylated in Mφs isolated from hyperlipidemia and T2DM ischemic muscles compared with controls. These results combined with mRNA expression and immunohistochemistry showed the predominance of proinflammatory M1-Mφs, compared with anti-inflammatory and proangiogenic M2-Mφs in hyperlipidemia and T2DM ischemic muscles. Conclusions: We found significant promoter hypomethylation of genes typical for proinflammatory M1-Mφs and hypermethylation of anti-inflammatory, proangiogenic M2-Mφ genes in hyperlipidemia and T2DM ischemic muscles. Epigenetic alterations modify Mφ phenotype toward proinflammatory M1 as opposed to anti-inflammatory, proangiogenic, and tissue repair M2 phenotype, which may contribute to the impaired adaptive vascular growth under these pathological conditions.